Impact of social media on secondary schools’ youths within Edo North, Edo State, Nigeria: A psychological perspective - Ngonso, Blessed Frederick; Ukhurebor, Kingsley Eghonghon; Egielewa, Peter Eshioke; Ndunagu, Juliana Ngozi; Yaah-Nyakko, Nana Kojo (Journal of Education and e-Learning Research, 2024)
This study examined the psychological impact of social media on Nigerian teenagers looking at how social media posts and tweets (messages) influence their perceptions towards migrating abroad. A survey research method was adopted to investigate the problem in its natural setting. Four secondary schools (SSs) within Edo North, Edo State, Nigeria were randomly selected from 56 government-owned SSs for the study. A questionnaire was used as a data collection instrument to obtain respondents' views (data) which was later analysed using SPSS. Spearman correlation and Pearson's R were used to measure the two hypotheses symmetrically. The chi-square was then used to test the results. According to their opinions (data collected), the findings of the study revealed that Nigerian teenagers of school age have access to social media, prefer text, video and audio kinds of information and mostly prefer Facebook to other social media networking sites. After analysing the tested hypotheses, the researcher concludes that there is a significant relationship between social media messages and Nigerian teenagers’ desire to travel abroad. Hence, social media messages or information affect their mental construct negatively which could be compared to mental slavery and they made some recommendations that would assist in mitigating these impacts.